Catalytic Effect of Cetyltrimethylammonium Bromide on the Oxidation of Tetraethylene Glycol by Chloramine-T in Acetic Acid Medium - SHARMA, VANDANA; SHARMA, K.V.; BHAGWAT, V.W. (Asian Journal of Chemistry, 2010)
The kinetics and mechanism of cetyltrimethylammonium bromide catalyzed oxidation of tetrathylene glycol [2,2'-(oxibis(ethylenoxy)- diethanol)] by chloramine-T in acetic acid medium have been investigated. The reaction has first order dependence on chloramine-T and fractional order for tetraethylene glycol with excess concentration of other reactants. The catalytic effect due to cetyletrimethylammonium bromide has been studied. The small salt effect and increase in the reaction rate with increasing dielectric constant suggest the involvement of neutral molecule in the rate-determining step. Addition of p-toluene sulfonamide retards the reaction rate. The effect of chloride ion on the reaction also studied. The effect of temperature on the reaction has been investigated in the temperature range 318-338 K and thermodynamic parameters are calculated from the Arrhenious plot. A tentative mechanism consistent with the experimental results has been proposed.